Corrigendum: A matter of life or death: Productively infected and bystander CD4 T Cells in early HIV infection - Cao, Dechao; Khanal, Sushant; Wang, Ling; Li, Zhengke; Zhao, Juan; Nguyen, Lam Nhat; Nguyen, Lam Ngoc Thao; Dang, Xindi; Schank, Madison; Thakuri, Bal Krishna Chand; Zhang, Jinyu; Lu, Zeyuan; et al. (Frontiers in Immunology, 2022)
Correction of Fig.1D representative dot plots.